Commodity prices just a click away - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Commodity prices just a click away, Business Line, Internet edition, June 2002 Farmers in Andhra Pradesh can now check out the prices of various commodities in different agricultural market yards in the State through the Internet or telephon